Exhaustive test sets for algebraic specifications. (27th January 2016) - Aiguier, Marc; Arnould, Agnès; Gall, Pascale Le; Longuet, Delphine
Summary: In the context of testing from algebraic specifications, test cases are ground formulas chosen amongst the ground semantic consequences of the specification, according to some possible additional observability conditions. A test set is said to be exhaustive if every programme P passing all the tests is correct and if for every incorrect programme P, there exists a test case on which P fails. Because correctness can be proved by testing on such a test set, it is an appropriate basis for the selection of a test set of practical size. The largest candidate test set is the set of observable consequences of the specification. However, depending on the nature of specifications and programmes, this set is not necessarily exhaustive. In this paper, we study conditions to ensure the exhaustiveness property of this set for several algebraic formalisms (equational, conditional positive, quantifier free and with quantifiers) and several test hypotheses. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this paper, we study the conditions to ensure the exhaustiveness property of the set of observable consequences for several algebraic formalisms and several test hypotheses. Such a property is essential in testing because it prevents from rejecting a correct program or dually to accept an incorrect program. Hence, exhaustive test sets, when they exist, are appropriate to start the process of selecting test sets of reasonable size.